MANAJEMEN PENGEMBANGAN KOMPETENSI KEPRIBADIAN DAN LEADERSHIP GURU PENDIDIKAN AGAMA ISLAM - M. Hanif Satria Budi (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2018)
The management of teacher competence development is a fundamental requirement in educational institutions. The aspects that are related to teachers are still a problem and should be addressed. One of them is the personality and leadership competence of Islamic Education (PAI) / Religious teacher, namely professional, pedagogical, and social competence. Personality competence becomes a very important issue because this competence becomes the basis for every teacher in performing the duties, as well as the leadership competence becomes the basis of PAI / Religious teacher in implementing learning and developing Islamic culture in the school This research aims at analyzing the management of teacher personality and leadership competency development more broadly and deeply at SMAN 3 Malang and MAN 1 Ngawi, with coverage: (1) the orientation of personality and teacher leadership development of PAI / Religious teacher, (2) the management of Personality competency development planning and teacher leadership of PAI / Religious teacher, (3) the management of implementation of personality and leadership competence development of teacher of PAI / Religious teacher, and (4) the evaluation and sustainable of personality competence and leadership development of teacher of PAI / Religious teacher. The research was conducted in SMAN 3 Malang and MAN 1 Ngawi and used qualitative approach with multisite types. Data collection was done using interviews, observation, and documentation. Data analysis techniques included data reduction, data presentation, and data verification. To check the data validity of the researcher used data triangulation technique. The informants in this research were principals, vice principals, general teachers, and teacher of PAI / religious The results of this research indicated that: (1) the orientation of the development of teacher personality and leadership competencies at SMAN 3 Malang and MAN 1 Ngawi is based on the sub indicators in each competence; (2) the management of development planning of personality competency and teacher leadership at SMAN 3 Malang and MAN 1 Ngawi is the involvement of school principal, vice chairman, UPM chairman, and head of field. The planning stage is the identification of problems, determining the needs of evelopment program dplanning, program implementation, and evaluation. The last of the planning is done in 3 lines namely short-term, long-term, and incidental planning; (3) the developments of personality competence and teacher leadership at SMAN 3 Malang and MAN 1 Ngawi are 2 stages, there are routine and incidental. The sources of development implementation are from the internal that is done by the school, and externally is done by the government and related ministries. the form of development included training, training, workshops, advanced studies, reading, spiritual religious activities, rewards, and motivation; (4) the evaluation and sustainable of the development of teacher personality and leadership competency at SMAN 3 Malang and MAN 1 Ngawi is done by school principal with the teacher performance evaluation, teacher diary, motivation, and guidance of school principal.